CD200 genotype is associated with clinical outcome of patients with multiple myeloma - Gonzalez-Montes, Yolanda; Osca-Gelis, Gemma; Rodriguez-Romanos, Rocío; Villavicencio, Alicia; González-Bártulos, Marta; Llopis, Francesca; Clapes, Victòria; Oriol, Albert; Sureda, Anna; Escoda, Lourdes; Sarrà, Josep; Garzó, Ana; et al. (Frontiers in Immunology, 2024)
Immune dysfunction in patients with MM affects both the innate and adaptive immune system. Molecules involved in the immune response pathways are essential to determine the ability of cancer cells to escape from the immune system surveillance.However, few data are available concerning the role of immune checkpoint molecules in predicting the myeloma control and immunological scape as mechanism of disease progression. We retrospectively analyzed the clinical impact of the CD200 genotype (rs1131199 and rs2272022) in 291 patients with newly diagnosed MM. Patients with a CD200 rs1131199 GG genotype showed a median overall survival (OS) significantly lower than those with CC+CG genotype (67.8 months versus 94.4 months respectively; p: 0.022) maintaining significance in the multivariate analysis. This effect was specially detected in patients not receiving an autologous stem cell transplant (auto-SCT) (p < 0.001). In these patients the rs1131199 GG genotype negatively influenced in the mortality not related with the progression of MM (p: 0.02) mainly due to infections events.